2000
DOI: 10.1046/j.1460-9568.2000.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

SDF‐1α‐mediated modulation of synaptic transmission in rat cerebellum

Abstract: The functional expression of the seven-transmembrane domain G protein-coupled chemokine receptor CXCR-4/fusin in rat nerve cell was demonstrated by staining with a polyclonal anti-CXCR-4 Ab, and by evaluating the calcium responses to the physiological agonist stromal-derived cell factor-1alpha (SDF-1alpha) in both cerebellar granule cells in culture and Purkinje neurons (PNs) in cerebellar slices. Cerebellar glial, granule and Purkinje cells showed a pronounced staining for CXCR-4. Furthermore, cultured granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 39 publications
5
97
0
1
Order By: Relevance
“…Several studies have recently suggested that, beyond their classical involvement in neuroinflammatory and infectious processes, chemokines may play additional roles in the CNS, such as regulation of neuronal survival, differentiation, synaptic transmission, and plasticity (Meucci et al, 1998;Asensio and Campbell, 1999;Limatola et al, 2000;Bezzi et al, 2001;Lu et al, 2002;Stumm et al, 2002). In analogy to what is observed in hematopoietic cells (Broxmeyer et al, 2001), emerging data indicate that SDF-1μ can regulate proliferation and maturation of developing neurons (Zou et al, 1998;Klein et al, 2001;Lu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently suggested that, beyond their classical involvement in neuroinflammatory and infectious processes, chemokines may play additional roles in the CNS, such as regulation of neuronal survival, differentiation, synaptic transmission, and plasticity (Meucci et al, 1998;Asensio and Campbell, 1999;Limatola et al, 2000;Bezzi et al, 2001;Lu et al, 2002;Stumm et al, 2002). In analogy to what is observed in hematopoietic cells (Broxmeyer et al, 2001), emerging data indicate that SDF-1μ can regulate proliferation and maturation of developing neurons (Zou et al, 1998;Klein et al, 2001;Lu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Limatola C et al (2000) first reported that Purkinje neurons in cerebellar slices responded to CXCL12 application by a slow inward current followed by an increase of both intracellular Ca 2+ and spontaneous synaptic activity. The same group reported that the amplitude of evoked excitatory postsynaptic currents (EPSC) of Purkinje neurons was reversibly reduced by CXCL12 application (Ragozzino D et al, 2002).…”
Section: Neuromodulationmentioning
confidence: 99%
“…Several studies have demonstrated that chemokines CXCL1, CXCL8, or CXCL12 regulate neurotransmitter release or modulate ion channel activity at both the presynaptic and postsynaptic levels. 36,37 Moreover, a recent study has reported that CX3CL1, a chemokine constitutively expressed in the CNS (along with CXCL12 and CXCL14), is a potent neuromodulator of evoked excitatory synaptic transmission. 38 Beyond their role in the CNS under physiological conditions, chemokines and chemokine receptors are studied primarily as mediators of CNS pathologies, especially those with an inflammatory component such as multiple sclerosis (MS).…”
Section: Chemokines and Chemokine Receptors In The Central Nervous Symentioning
confidence: 99%